Peran Komunikasi Efektif Untuk Meningkatkan Kolaborasi di Lingkungan Pendidikan Indonesia - Eka Putri, Junita Hanum; Adella, Mutia; Putri, Dhea Aulia; Walidaini, Ichsani; Nasution, Inom (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Effective communication is an important component in creating productive collaboration in an educational environment. This research aims to identify the role of effective communication in improving collaboration in Indonesian schools, examine the factors that influence successful communication, and provide practical recommendations for implementation at various levels of education. The methodology used includes a qualitative descriptive approach with a phenomenological approach. The research results show that clear, open, and timely communication between teachers, students, and parents is the main key in building effective collaboration. The main obstacles found include differences in perception, lack of time, and technological limitations. To overcome this obstacle, communication training for teachers, the use of communication technology, and school policies that support the active participation of all parties are needed. This research concludes that the implementation of effective communication can increase trust and cooperation, which will ultimately improve the quality of education in Indonesia. Recommendations include communication training, use of technology, development of supporting policies, increased parental involvement, and ongoing evaluation.